Case report: Clitoromegaly as a consequence of Congenital Adrenal Hyperplasia. An accurate medical and surgical approach - Fernandez-Aristi, Augusto Rafael (2018)
We present a case of a woman with a history of Congenital Adrenal Hyperplasia (CAH) diagnosed at the age of 12, who was referred to our unit for surgical treatment. Despite the initial diagnosis was an indirect inguinal hernia, it was a misdiagnosis. Once in our service, this was corrected into clitoromegaly secondary to CAH. Physical examination and imaging test discarded other abnormalities, such as secondary effects androgenization. Regarding surgical treatment, the techniques used were Spencer and Allen combined with Kumar, which are the most used for clitoroplasty but also less used in Peru.